1995
DOI: 10.1128/mcb.15.4.2304
|View full text |Cite
|
Sign up to set email alerts
|

AH/PH Domain-Mediated Interaction between Akt Molecules and Its Potential Role in Akt Regulation

Abstract: The cytoplasmic serine-threonine protein kinase coded for by the c-akt proto-oncogene features a protein kinase C-like catalytic domain and a unique NH 2 -terminal domain (AH domain). The AH domain is a member of a domain superfamily whose prototype was observed in pleckstrin (pleckstrin homology, or PH, domain). In this communication, we present evidence that the AH/PH domain is a domain of protein-protein interaction which mediates the formation of Akt protein complexes. The interaction between c-akt AH/PH d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 25 publications
(26 reference statements)
4
131
1
Order By: Relevance
“…It has been demonstrated that the PH domain of PKB mediates interaction between PKB molecules, playing a role in regulation [51]. Transfection of COS-1 cells with an epitope-tagged C-terminally truncated PKB allows co-immunoprecipitation of full-length PKB.…”
Section: Pkb Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the PH domain of PKB mediates interaction between PKB molecules, playing a role in regulation [51]. Transfection of COS-1 cells with an epitope-tagged C-terminally truncated PKB allows co-immunoprecipitation of full-length PKB.…”
Section: Pkb Complexesmentioning
confidence: 99%
“…In Madin-Darby canine kidney (MDCK) cells it has been demonstrated that detachment from the matrix leads to a rapid decrease in the levels of PI-3K products and PKB activity, and vice versa for attachment [120]. Introduction of active mutants of p21ras, PI-3K or PKB protects MDCK cells from apoptosis in suspension, while inhibition of PI-3K with LY294002, or PKB by transient expression of the PH domain alone [51], resulted in enhanced apoptosis of adhered cells [120]. These data suggest a model whereby through engagement of integrins by extracellular-matrix interactions, PI-3K becomes activated and provides a protective signal through activation of PKB.…”
Section: Anoikismentioning
confidence: 99%
“…Akt can directly phosphorylate BAD on S136 (ref. 94,95), causing its inactivation and inability to interact with antiapoptotic members of the Bcl-2 family of proteins (Bcl-2, Bcl-X L ). 96,97 Activated Akt can inhibit the release of cytochrome c from the mitochondria, which is a potent activator of the apoptotic caspase cascade.…”
Section: Targeting Translation Governed By Pi3k Pathway Am Martelli Ementioning
confidence: 99%
“…[51][52][53][54][55][56] Generally, PTEN absence in breast carcinomas is due to gene promoter hypermethylation [51][52][53][54][55] or loss of heterozygosity, 53 whereas PTEN mutations are exceptional in sporadic neoplasms. 57 Loss of 51,56 as in our series where Akt, present in 28% of tumors, was more frequently associated with growth factor receptors than with the PTEN pathway. 52,57 Recently, pAkt overexpression was described in 33% of in situ and 38% of ductal invasive breast carcinomas, although without any significant clinicopathological relationship, 56 as in our cases.…”
Section: Heterogeneity In Basal Breast Carcinomas E Lerma Et Almentioning
confidence: 99%